2008
DOI: 10.1016/j.ejcts.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of life, physical activity, and symptomatic status one year after myocardial revascularization for stable angina

Abstract: Elderly patients have the same improvement of their symptomatic status as younger patients. However despite this improvement they have less benefit from CABG regarding to their quality of life and physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
2
25
0
1
Order By: Relevance
“…Men who undergo CABG at a later age have similar decreased functional status and exercise capacity, so age may very well be a confounding factor when examining gender differences. 36 We did note that these general findings were remarkably similar between all of the studies we reviewed that had substantial numbers of women enrolled. Additional research is warranted to tease out reasons for these observed differences between gender and age groups.…”
Section: Discussionsupporting
confidence: 53%
“…Men who undergo CABG at a later age have similar decreased functional status and exercise capacity, so age may very well be a confounding factor when examining gender differences. 36 We did note that these general findings were remarkably similar between all of the studies we reviewed that had substantial numbers of women enrolled. Additional research is warranted to tease out reasons for these observed differences between gender and age groups.…”
Section: Discussionsupporting
confidence: 53%
“…The period [11,12]. In our series we observed value of 1.38, which can be attributed to the presence of angina or anxiety in the preoperative period, because most of the population had coronary artery obstruction and had undergone coronary artery bypass grafting [13,14].…”
Section: Resultsmentioning
confidence: 68%
“…For this review, we excluded the four studies generated by our own group [3][4][5][6]. The other 29 studies were screened for the three respective study points .…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three papers were found using the PubMed search [3][4][5][6]. For this review, we excluded the four studies generated by our own group [3][4][5][6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation